A STUDY OF STABLE WORD COMBINATIONS: DIVERSITY AND TYPES IN CURRENT RUSSIAN (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article is devoted to the types of phraseological units in the modern Russian language, their classification and functional features. The work examines the main groups of phraseological units, including idioms, proverbs and sayings, stable combinations, phraseological turns and catchphrases. Each category is analyzed, emphasizing their role in enriching the language and expressing thoughts. Particular attention is paid to the change in the use of phraseological units in the context of modern communication and the influence of cultural factors. The article highlights the importance of phraseology for understanding language as a living and dynamic phenomenon and suggests directions for further research in this area.